Mathematical model of color optoelectronic measurement - Horoshaylo, Yuriy Evgeniyovych; Yefymenko, Sergіy Andrіyovich; Sezonova, Irina Konstantinovna (NTU "KhPI", 2018)
The work is devoted to the analysis of methods of mathematical modeling, one of the most important in human life – the organ of vision, which accounts for more than 90% of all incoming information about the external world. The human eye is a unique (natural) natural apparatus. Therefore, the principles of his work have long attracted the attention of scientists. At the heart of the tasks posed in this paper were questions closely related to the theory of human perception of color. Still I.Newton the ground for creation of linear model of color vision was prepared. For the first time one of such models was suggested by T. Young. But T. Young was interested not so much in the psychophysical side of the phenomenon as in the physiological aspect, therefore, from the point of view of psychophysics, his results look like an episode. The most consistent continuation of Newton's ideas was Maxwell, who attempted to experimentally determine a specific kind of weight functions that characterize the sensitivity of the eye to radiation with different wavelengths, called spectral sensitivity functions of the eye. The first attempt to create an axiomatic theory of the eye was undertaken by Grassmann. Relying on Newt on's results and his idea of a "null-organ", he formulated the laws of color vision – the law of additivity, the law of three-dimensionality, the law of continuity. Starting from these laws, Schrödinger attempted to derive Newton's transformations from them in a purely formal way. However, the imperfect ion of the mathematical algorithm used by him and the formulation of the laws of vision did not allow him to do this correctly enough. But on the whole, Schroedinger's research should be seen as an essential step in the development of the theory of vision. Based the analysis of existing mathematical methods of vision research, the present work accepts the interpretation of input signals in the form of Hilbert spaces. The main reason for this is as follows. As studies of sensory systems show, the description of the work of sense organs leads us to linear functionals whose general form is known in Hilbert spaces or in spaces of type Lp. The authors on of the paper propose a method and an apparatus for colorimetric measurements. The main element of the color tone recognition device is a sensor (color sensor) in which to increase the sensitivity and reliability of measurements, as well as simplify the tuning process, not three, but more (number) photodetectors are used.

Робота присвячена аналізу методів математичного моделювання однією з найбільш важливих в життєдіяльності людини – органу зору, на частку якого припадає понад 90% всієї що надходить інформації про зовнішній світ. Людське око є унікальний (природний) природний апарат. Тому принципи його роботи здавна привертали увагу вчених. В основі поставлених в даній роботі завдань лежали питання, тісно пов'язані з теорією сприйняття кольору людиною. Грунтуючись на аналізі існуючих математичних методів дослідження зору в даній роботі прийнята інтерпретація вхідних сигналів у вигляді Гільбертових просторів. Основна причина подібного в наступному. Як показують дослідження сенсорних систем, опис роботи органів почуттів призводить нас до лінійним функціоналом, загальний вигляд яких відомий в Гільбертових просторах або в просторах типу Lp. Авторами статті пропонується метод і пристрій для колориметричних вимірювань. Основним елементом пристрою розпізнавання колірних відтінків є датчик (сенсор) кольору, в якому для збільшення чутливості і достовірності вимірювань, а також спрощення процесу налаштування, використовується не три, а більшу кількість (число) фотоприймачів.
Математична модель колориметрії
Keywords: colorimetry; perception of color; sensory systems; color coordinates; photodetector; light sensor; колориметрія; сприйняття кольору; сенсорні системи; колірні координати; фотоприймач; датчик світла